Association of whole grain food consumption with lung cancer risk: a prospective cohort study - Kanran Wang; Junhan Zhao; Dingyi Yang; Mao Sun; Yongzhong Wu; Wei Zhou (Cancer Cell International)
Abstract Background Whether the intake of whole grain foods can protect against lung cancer is a long-standing question of considerable public health import, but the epidemiologic evidence has been limited. Therefore we aim to investigate the relationship between whole grain food consumption and lung cancer in the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial (PLCO) cohort. Methods Diet was assessed with a self-administered Diet History Questionnaire (DHQ) at baseline. All incident lung cancer cases were pathologically verified. Hazard ratios and 95% confidence intervals for lung cancer risk associated with whole grain food consumption were estimated by Cox proportional hazards regression. Results During a median follow-up of 12.2 years, a total of 1,706 incident lung cancer events occurred, including 1,473 (86.3%) cases of non-small cell lung cancer (NSCLC) and 233 (13.7%) of small cell lung cancer (SCLC). After multivariate adjustment, comparing the highest quarter of consumption of whole grain foods to the lowest quarter, a 16% lower rate (HR 0.84, 95% CI 0.73–0.98) of lung cancer risks and a 17% lower rate (HR 0.83, 95% CI 0.69–0.98) for NSCLC were found, but no significant difference was shown for SCLC (HR 0.95, 95% CI 0.63–1.44). These results were consistently observed after a large range of subgroup and sensitivity analyses. A linear dose-response pattern was shown for lung cancer, NSCLC, and SCLC (P for non-linearity > 0.05). Conclusions In this large prospective cohort study, whole grain food consumption was associated with reduced lung cancer and NSCLC. Our findings suggest a potential protective role of whole grain foods against lung cancer.